Powering up developing countries through integration? - Emmanuelle Auriol; Sara Biancini (Center for Economic Studies and ifo Institute (CESifo), 2012)
Power market integration is analyzed in a two countries model with nationally regulated firms and costly public funds. If generation costs between the two countries are too similar negative business-stealing outweighs efficiency gains so that following integration welfare decreases in both regions. Integration is welfare-enhancing when the cost difference between the two regions is large enough. The benefit from export profits increases total welfare in the exporting country, while the importing country benefits from lower prices. This is a case where market integration also improves the incentives to invest compared to autarky. The investment levels remain inefficient though. With generation facilities over-investment occurs sometimes, while systematic under-investment occurs for transportation facilities. Free-riding reduces the incentives to invest in these public-good components, while business-stealing tends to reduce the capacity for financing new investment.
Keywords: L43; L51; F12; F15; R53; 330; regulation; competition; market integration; investment; electricity; Energiemarkt; Marktintegration; Investition; Elektrizitätswirtschaft; Regulierung; Zwei-Länder-Modell; Theorie; Industriestaaten